2021
DOI: 10.3389/fimmu.2020.587617
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammation in Pregnant Women With Latent Tuberculosis Infection

Abstract: BackgroundRecent studies in adults have characterized differences in systemic inflammation between adults with and without latent tuberculosis infection (LTBI+ vs. LTBI−). Potential differences in systemic inflammation by LTBI status has not been assess in pregnant women.MethodsWe conducted a cohort study of 155 LTBI+ and 65 LTBI− pregnant women, stratified by HIV status, attending an antenatal clinic in Pune, India. LTBI status was assessed by interferon gamma release assay. Plasma was used to measure systemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 34 publications
(54 reference statements)
2
14
0
Order By: Relevance
“…While our study seems to confirm this global decline in the IFN-g responses observed from other longitudinal studies in pregnant women (7,20), the additional parallel comparison of the IFN-g response with that of control non-pregnant women of similar age in our study showed that this IFN-g response is strongly requested following an exposition to M. tuberculosis in pregnant women. Similar immune responses with a strong IFN-g production were observed among LTBI+ pregnant women in India after the comparison with LTBI-pregnant women (10). This strong activation of IFN-g following an exposition to M. tuberculosis and observations made on the antiviral immune response in pregnant woman seems to confirm the fact that pregnancy is not a period of immunosuppression notably for Th1 but a temporary attenuation in immune responses characterized by a strengthening of innate immune barriers and a concomitant reduction in pro-inflammatory immunity that is resumed when exposed to infections (21,22).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…While our study seems to confirm this global decline in the IFN-g responses observed from other longitudinal studies in pregnant women (7,20), the additional parallel comparison of the IFN-g response with that of control non-pregnant women of similar age in our study showed that this IFN-g response is strongly requested following an exposition to M. tuberculosis in pregnant women. Similar immune responses with a strong IFN-g production were observed among LTBI+ pregnant women in India after the comparison with LTBI-pregnant women (10). This strong activation of IFN-g following an exposition to M. tuberculosis and observations made on the antiviral immune response in pregnant woman seems to confirm the fact that pregnancy is not a period of immunosuppression notably for Th1 but a temporary attenuation in immune responses characterized by a strengthening of innate immune barriers and a concomitant reduction in pro-inflammatory immunity that is resumed when exposed to infections (21,22).…”
Section: Discussionsupporting
confidence: 71%
“…Second, we have not investigated other TB-specific cytokines. There are changes among other cytokines that are specific to pregnancy ( 10 ). The next steps for this study would be to better understand the impact of these variations by assessing other cytokines and biomarkers of LTBI and/or progression to active TB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted a longitudinal cohort study of pregnant women (PRACHITi [Pregnancy Associated Changes in Tuberculosis Immunology] study) in Pune, India, from June 27, 2016, to December 9, 2019. 7 We enrolled adult pregnant women aged 18 to 40 years and between 13 and 34 weeks of gestation (confirmed by early pregnancy ultrasonography) who were receiving antenatal care at Byramjee Jeejeebhoy Government Medical College, a tertiary care hospital that serves primarily low-income populations and is a referral center for HIV care. The study excluded pregnant women with active tuberculosis or severe anemia at entry, as well as women who were taking antibiotics for more than 14 days, had a history of an autoimmune or immunosuppressive disease, or were taking immunosuppressive medication.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, elevated levels of biomarkers of systemic inflammation have also been reported in persons with LTBI [ 42 45 ], and a recent study revealed differences in peripheral blood cytokine profiles among Indian pregnant women with LTBI compared to TB-uninfected women [ 46 ]. Furthermore, recent observational studies have suggested associations between LTBI and myocardial infarction and atherosclerosis [ 47 , 48 ], which has been suggested to be linked to chronic low-grade inflammation.…”
Section: Discussionmentioning
confidence: 99%